Failing up: How failure in a game environment promotes learning through discourse. (December 2018) - Anderson, Craig G.; Dalsen, Jen; Kumar, Vishesh; Berland, Matthew; Steinkuehler, Constance
Highlights: Number of level failures in an educational game shown as a positive predictor of learning gains. Level failures in an educational game shown to lead to collaborative discourse on embedded learning material. Educational games reflected as an environment for frequent opportunity for productive failure. Abstract: In many video games, failure can be an indicator that you are, in some way, progressing (Juul, 2013). This is often through challenging content which may take multiple attempts to complete. In education failure can also be seen as an underpinning of learning. In this study, we investigate the influence of failure on thinking skills in an educational video game. We analyze gameplay patterns and surrounding discourse of 88 middle school students playing Virulent, an educational game designed to teach virology to investigate the role of level failures in learning. Participants were separated into groups of 3–4 to roleplay as scientists and engaged in discussions on how to stop a virus while playing Virulent. To investigate the role of failure in learning in our camp, gameplay data were analyzed for patterns in player level failures while discourse around level failures was analyzed for the development of sense making. The current work presents analyses showing that a higher number of failures before initial success at levels across the game predict greater learning gains than time on task measures. This finding is then tied to discourse that shows that after encountering failures, players were often led to group discussions on relevant game mechanics with embedded virology content. This suggests that initial failures at educational game levels may help initiate collaborative discourse that promotes understanding of the program learning goals. These findings are discussed through the lens of productive failure (Kapur, 2008) and implications for educational game design are explored.